Talent Management In Multinational Companies In Malaysia - Mohammadi Sepahvand, Helia (2011)
The aims of this study is to determine the techniques used by organizations, the aims of this study is to determine the techniques used by organizations to recruit and select, develop and retain talent. The study also examines the relationship between recruitment and selection, development and retention techniques used by organizations and their talent management. Moreover, this study revealed that the recruitment and selection techniques used by these organizations are the significant predictor of talent management.